Arbuscular mycorrhizal fungi associated with Amaranthus dubius mart.ex thell and Gomphrena globosa L . (Bangladesh Journal of Scientific and Industrial Research, 2014)
Arbuscular mycorrhizal fungi are found associated with more than 80% of the plants. But most of the studies show that Amaranthaceae is non mycorrhizal. The present study states the presence of arbuscular mycorrhizal association with Amaranthus dubius Mart ex Thell and Gomphrena globosa L which belong to Amaranthaceae. The plants were screened for the examination of presence of arbuscules, vesicles in the roots and spores in the rhizosphere soil which help to know that mycorrhiza is associated with Amaranthaceae species. DOI: http://dx.doi.org/10.3329/bjsir.v49i1.18857 Bangladesh J. Sci. Ind. Res. 49(1), 59-62, 2014